Edukasi dan Pengelolaan Sampah Organik dan Anorganik di Wilayah Pesisir Pantai Botutonuo Sebagai Upaya Konservasi Lingkungan - Moh. Khamal Salote; Sukirman Rahim; Syam S. Kumaji; Wiwin Kobi (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
The Botutonuo Beach coastal area is a prime tourist destination in Bone Bolango Regency that faces issues with the accumulation of organic and inorganic waste caused by tourist activities and debris carried in by ocean currents. This situation threatens to degrade environmental quality, detract from the area's aesthetic appeal, and compromise the sustainability of the coastal ecosystem. This community service initiative aims to enhance public knowledge, awareness, and participation regarding waste management as a means of coastal environmental conservation. The implementation process comprised pre-implementation, implementation, and post-implementation phases, involving community coordination, educational sessions on sorting and managing organic and inorganic waste, and a beach cleanup drive involving lecturers, students, and local residents. The results indicate an increased understanding among participants regarding the importance of waste sorting, reducing single-use plastic consumption, and applying the 3R principles (Reduce, Reuse, Recycle) in daily life. Furthermore, the beach cleanup successfully reduced waste accumulation in the coastal area and fostered a collective sense of responsibility for environmental preservation. This activity demonstrates that combining education with tangible action can drive behavioral changes within the community regarding the maintenance of coastal cleanliness. Therefore, sustainable education and waste management programs must be continued through collaboration among universities, local government, tourism operators, and the community to ensure Botutonuo Beach becomes a clean, healthy, and sustainable area.